2011
DOI: 10.1007/s11250-011-9915-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing reproductive performance of cows from different Nguni ecotypes in southern Mozambique

Abstract: The objective of this study was to assess the reproductive performance of two Nguni ecotypes (Nguni and Landim) raised in a subtropical environment to enhance strategies for livestock development and restocking programmes within the southern African region. Reproduction data collected between 1996 and 2009 from 365 cows of the Landim and Nguni ecotypes were analysed. From the results, ecotype, place of birth, year and season of birth/calving had significant effects on age at first calving (AFC) and calving int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Small-framed indigenous breeds, such as the Nguni, exhibit high reproductive fitness under poor nutritional conditions of Sub-Saharan Africa (Ndlovu et al, 2007). Under the Sub-Saharan African conditions, small-framed Nguni cattle reach puberty at younger age (about 16 months) and have shorter CI (about 370 days) compared with larger framed beef breeds such as the Drakensberger and Bonsmara (Maciel et al, 2011). As a result of their reproductive fitness, small-framed breeds such as Nguni, Bonsmara and the Tuli have gained ground in modern Sub-Saharan beef population (Strydom, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Small-framed indigenous breeds, such as the Nguni, exhibit high reproductive fitness under poor nutritional conditions of Sub-Saharan Africa (Ndlovu et al, 2007). Under the Sub-Saharan African conditions, small-framed Nguni cattle reach puberty at younger age (about 16 months) and have shorter CI (about 370 days) compared with larger framed beef breeds such as the Drakensberger and Bonsmara (Maciel et al, 2011). As a result of their reproductive fitness, small-framed breeds such as Nguni, Bonsmara and the Tuli have gained ground in modern Sub-Saharan beef population (Strydom, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These higher values in humid AEZ could have resulted from minimal nutritional stress to animals as these areas receive enough rainfall for forage growth (Mohamed-Saleem, 1995) and therefore resulting in higher milk production compared to dams in other AEZ's. Production performance in cattle differed between production locations (agro-ecological zones) (Tredeen et al, 1982;Maciel et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it is needful to note that, the age when a local cow calf is judged to be significant aspects that define the reproductive efficiency of the cow. For instance, a study from Mozambique reported that a local Nguni ecotype (cattle) at first calving age was 35.7 months with less calving interval of one year and two months (Maciel et al, 2012). Nonetheless, on the contrary, Tada et al (2013b) reported in their study that the local Nguni cattle breed which is calves at 31.5 months, but with a calving interval of approximately one year and four months.…”
Section: A Poor Breeding and Breeding Programmesmentioning
confidence: 95%